A Chemical Route to BiNbO4 Ceramics - Shlyakhtin, Oleg A.; Oh, Young-Jei (WILEY, 2009)
The liquid phase sintering of fine BiNbO4 powders allows to obtain dense ceramics with excellent microwave dielectric properties (epsilon=44-46; Q x f=16,500-21,600 GHz) at T >= 700 degrees C. The thermal decomposition of freeze-dried precursors results in the crystallization of a metastable beta'-BiNbO4 polymorph that transforms into a stable orthorhombic alpha-modification at T >= 700 degrees C. The dependence of sinterability on the powder synthesis temperature shows the maximum at 600 degrees C, corresponding to the formation of crystalline BiNbO4 powders with a grain size 80-100 nm. Sintering temperature reduction to 700 degrees C prevents the deterioration of silver contacts during co-firing with BiNbO4 ceramics. In situ scanning electron microscopy observation of the morphological evolution during sintering shows that the intense shrinkage soon after the appearance of a CuO-V2O5 eutectics-based liquid phase is accompanied by complete transformation of the ensemble of primary BiNbO4 particles.
Keywords: MICROWAVE DIELECTRIC-PROPERTIES; SINTERING BEHAVIOR; ELECTRICAL-PROPERTIES; CUO-V2O5 MIXTURES; SILVER ELECTRODES; CRYSTAL-STRUCTURE; SINGLE-CRYSTALS; LIQUID-PHASE; TAU(F) VALUE; V2O5